2023
DOI: 10.3390/su152416801
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences, Possible Sources, and Risk Impacts of Organochlorine Pesticides in Soil of Changchun Central Urban Area, Northeast China

Wei Zhao,
Jilong Lu,
Yawen Lai
et al.

Abstract: Eighteen organochlorine pesticides (OCPs) in soil samples from the Changchun central urban area, Northeast China were analyzed using accelerated solvent extraction combined with gas chromatography/mass spectrometry (ASE-GC/MS) for the purpose of elucidating their contamination status, distribution characteristics, influencing factors, and feasible dangers in this city region. The complete concentrations of OCPs ranged from 15.63 to 92.79 ng/g, with a geomean of 36.46 ng/g. Hexachlorocyclohexane(HCHs), dichloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…β-HCH, heptachlor epoxide, trans-chlordane and endrin were not found in any sample analysed, while other OCPs were detected in small amounts and in a limited number of soil samples (Table S1). The results are quite similar to those obtained by other authors in Mures , County in Romania [22] or in China [23], who found OCP residues in the range of tens of ng/g in soil samples. On the other hand, another study carried out in Mongolia [24] found OCP concentrations of the order of µg/g soil being 1000 times higher than the concentrations found in this study.…”
Section: Ocp Distribution and Potential Source Apportionmentsupporting
confidence: 91%
“…β-HCH, heptachlor epoxide, trans-chlordane and endrin were not found in any sample analysed, while other OCPs were detected in small amounts and in a limited number of soil samples (Table S1). The results are quite similar to those obtained by other authors in Mures , County in Romania [22] or in China [23], who found OCP residues in the range of tens of ng/g in soil samples. On the other hand, another study carried out in Mongolia [24] found OCP concentrations of the order of µg/g soil being 1000 times higher than the concentrations found in this study.…”
Section: Ocp Distribution and Potential Source Apportionmentsupporting
confidence: 91%